The Role of Parents in Character Education for Children: A Narrative Analysis by A.J. Greimas on the Youtube Channel Bestie Life-Ḥayātun afḍal - Emil Nurdiani; R. Edi Komaruddin; Yadi Mardiansyah (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
The YouTube channel Bestie Life – Ḥayātun Afḍal features inspirational stories that highlight the role of parents in guiding their children. This research aims to analyze the role of parents in character education for children through a review of actantial structure based on A.J. Greimas's narrative theory. The research method used is library research with a descriptive approach, focusing on the analysis of narrative texts. The data source for this research is a collection of stories from the Bestie Life – Ḥayātun Afḍal channel, namely "Kisah Nilai Hidupmu_ Qiṣṣatu Qīmat Ḥayātik", "Kisah yang Menenangkan Pikiranmu_ Qiṣṣatu Tahdi’u Dhihnak", and "Kisah yang Akan Membangkitkan Semangatmu_ Qiṣṣatu Satarfa‘u Ma‘nawiyyātak". The data collection technique was carried out using the note-taking method on data in the form of dialogue and situations. Data were collected through the note-taking method on dialogues and situations in the story. The research results show that the destinator (parents) actively play the role of life lesson givers, while the child as the receiver accepts the values of life. The presence of adjuvants (supporters) and traitors (obstacles) clarifies that the learning process in real life is not always easy. Thus, this channel not only serves as a medium of entertainment but also as an inspiring source of learning for parents and children in understanding and internalizing life values